Application of Advanced Quantum Dots Films in Optoelectronics - Guyot-Sionnest, Philippe; Tang, Xin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
From single-element detectors to array-format imagers, quantum dots and other thin optoelectronic films have played important roles in various fields including autonomous driving, industry inspection, remote sensing and biological imaging. This reprint focuses on fundamental and applied research on colloidal quantum dots and other thin-film optoelectronic materials including perovskites, lead chalcogenides, mercury chalcogenides and two-dimensional materials. The sensing spectrum covers X-ray, visible and infrared wavelengths. A diverse range of device configurations have been investigated such as photoconductors, photovoltaics and phototransistors.